The Influence of Culture in Determining Pregnancy Care: Official Village Midwives Versus Traditional Birth Attendants in Remote Area (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: The high rate of maternal and infant mortality in Indonesia in the past year can be influenced by the habits of the community who prefer Traditional Birth Attendants (TBAs) in the childbirth. In fact, TBAs are not health profession and do not have competency standards to assist with childbirth, thus increasing the risk of maternal and infant mortality. This article aimed to determine the influence of culture on the community’s habit of choosing TBAsor official village midwives (OVMs)in childbirth process in remote areas.Methods: A cross-sectional study was used. The respondents were mothers who gave birth in the last one year in one remote sub-district in Aceh. TBAs and official village midwiveswereobserved and indepth interviews were also conducted.Resultsand Discussions:The results of this study showed community attitudes about cultural influences during pregnancy, such as TBAs-assisted delivery is a cultural belief that must be followed.Hence, factors that influence the choice of mothers in using OVMs or TBAs:cultural beliefs and norms, and the role of the cultural leaders in making decisions. Conclusions: Culture plays an important role in influencing people who live in remote areas to choose TBAs rather than the OVMs.
Keywords: Culture, Official Village Midwives, Traditional Birth Attendants